1998
DOI: 10.1103/physrevd.58.054001
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric muon flux at sea level, underground, and underwater

Abstract: The vertical sea-level muon spectrum at energies above 1 GeV and the muon intensities at depths up to 18 km w.e. in different rocks and in water are calculated. The results are particularly collated with a great body of the ground-level, underground, and underwater muon data. In the hadron-cascade calculations, we take into account the logarithmic growth with energy of inelastic cross sections and pion, kaon, and nucleon generation in pion-nucleus collisions. For evaluating the prompt muon contribution to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 116 publications
(237 reference statements)
6
179
1
Order By: Relevance
“…Table 1 lists the authors and energy range of the reported absolute vertical intensity measurements. It is also shown if the experiment has been used by other reviews, namely "B" (Bugaev et al, 1998), "H&T" (Hebbeker and Timmermans, 2002) and in the Particle Data Group "PDG" (Nakamura et al, 2010). For H&T we report also the final normalization Flint et al (1972), Jakeman (1956), Wilson (1959), Gettert et al (1993), Dmitrieva et al (2006), Crokes and Rastin (1972). of material crossed by the particle in such detectors increases with increase of zenith angle, so the threshold energy for multidirectional muon telescopes depends on θ.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…Table 1 lists the authors and energy range of the reported absolute vertical intensity measurements. It is also shown if the experiment has been used by other reviews, namely "B" (Bugaev et al, 1998), "H&T" (Hebbeker and Timmermans, 2002) and in the Particle Data Group "PDG" (Nakamura et al, 2010). For H&T we report also the final normalization Flint et al (1972), Jakeman (1956), Wilson (1959), Gettert et al (1993), Dmitrieva et al (2006), Crokes and Rastin (1972). of material crossed by the particle in such detectors increases with increase of zenith angle, so the threshold energy for multidirectional muon telescopes depends on θ.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…Its quantification is essential for the cosmic ray physics as well as for neutrinos physics. On one hand, the flux of cosmic ray muons in the atmosphere, underground and underwater provides a way to testing the inputs of nuclear cascade models, that is, parameters of the primary cosmic ray flux (energy spectrum, chemical composition, ...) and particle interactions at high energies [3]. On the other hand, the flux of atmospheric neutrinos and muons at very high energies provides the main background of searches for the muons neutrinos from extra-galactic neutrino sources in the neutrinos experiments JHEP00(2007)000 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The same is for the sea-like IC model: x c+c = 0.024. For applications in cosmic ray physics (in particular, for calculations of atmospheric spectra of leptons (see, e.g., [23,24])) we need the dependence of dN/dx F on x F , so, we integrate (6) on p ⊥ and change the variables, using the relation…”
Section: Resultsmentioning
confidence: 99%